Epidemiology of unintentional fatal drowning among migrants in Australia. (26th April 2021) - Willcox‐Pidgeon, Stacey; Franklin, Richard C.; Leggat, Peter A.; Devine, Susan
Abstract: Objective : This study aimed to describe the epidemiology and risk factors contributing to drowning among migrants in Australia. Methods : A total population retrospective epidemiological study of unintentional drowning deaths in Australia between 1 July 2009 and 30 June 2019 of people born outside Australia (migrants). Cases were extracted from the National Coronial Information System. Descriptive statistics, chi‐square and relative risk were calculated. Crude drowning rates were based on country of birth and population in Australia. Results : There were 572 migrant deaths over the study period, 28.9% of total drowning deaths, 82.9% were male. Twenty‐one per cent were aged 25–34 years and 40.8% had lived in Australia for 20+ years. Migrants at highest risk of drowning were from: South Korea (2.63/100, 000 95%CI: 0.85–8.25), Taiwan (2.29/100, 000 95%CI: 0.27–13.44), and Nepal (2.15/100, 000 95%CI: 0.23–11.55). Migrants were more likely to drown when around rocks (p<0.001) compared with Australian‐born people, who most frequently drowned in rivers (p<0.001). Conclusions : Migrants are not over‐represented in drowning statistics. However, unique trends were found for drowning among migrants based on country of birth and length of time in Australia. Implications for public health : Holistic drowning prevention strategies and policies are required to effectively lower drowning risk among migrant communities.